CYBERCRIME AND DATA PROTECTION LAWS IN PAKISTAN: CHALLENGES, LEGAL FRAMEWORK, AND THE NEED FOR EFFECTIVE DIGITAL RIGHTS PROTECTION - Zaheer Iqbal Cheema; Muhammad Azeem Farooqi; Gul Sher Butt (Policy Journal of Social Science Review, 2026)
Digital technologies have revolutionized social, economic and governmental activities in Pakistan. The expansion of the internet, smart phones, online banking, e-commerce sites and digital communication networks have provided positive opportunities for economic development and social interaction. The digital transformation, however, has also yielded new manifestations of criminality, such as those involving cyber fraud, unauthorized use of information systems, ID theft, online harassment, data breach and other crimes that are technology-based. With the rising trend of dependence on digital platforms and low awareness among the public on cybersecurity practices, cybercrime is becoming a major problem for Pakistan. To confront these problems, Pakistan enacted the Prevention of Electronic Crimes Act (PECA), 2016, which is an all-embracing legislation to combat electronic crimes and digital offences. While PECA has laid a solid ground for the regulation of cybercrime, there are also some issues that need to be addressed in relation to enforcement mechanisms, institutional capacity, privacy protection, and balancing cybercrime security measures with basic human rights. The study analyzes the existing legislation related to cybercrime and data protection in Pakistan, highlighting the effectiveness of the laws, implementation challenges, and the need for more robust protection of digital rights. The study calls for a comprehensive data protection regime in the country, enhancement of institutional capacities and a rights-based approach to cybersecurity regulation. Good cyber governance should not only safeguard against digital risks faced by individuals and institutions, but also respect privacy, freedom of expression and due process in compliance with constitutional and international human rights principles. Keywords: Cybercrime, Data Protection, Prevention of Electronic Crimes Act 2016, Digital Rights, Privacy, Cybersecurity, Pakistan, Information Technology Law.